2006
DOI: 10.1523/jneurosci.1285-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Stereological Analysis of Amygdala Neuron Number in Autism

Abstract: The amygdala is one of several brain regions suspected to be pathological in autism. Previously, we found that young children with autism have a larger amygdala than typically developing children. Past qualitative observations of the autistic brain suggest increased cell density in some nuclei of the postmortem autistic amygdala. In this first, quantitative stereological study of the autistic brain, we counted and measured neurons in several amygdala subdivisions of 9 autism male brains and 10 age-matched male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
277
4
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(313 citation statements)
references
References 34 publications
27
277
4
5
Order By: Relevance
“…Even though the hypothesis that the amygdala might underlie abnormal fear processing in autism has been brought forward recently (Amaral et al, 2003;Schumann and Amaral, 2006), the present study is the first to show that fear memories are greatly enhanced, overly generalized to novel stimuli, and harder to extinguish in an animal model of autism. These results are in fact also consistent with some less cited autistic features such as enhanced fears and phobias originally described by Kanner (1943) and reported in some more recent studies (Muris et al, 1998;Gillott et al, 2001;Evans et al, 2005).…”
Section: A Novel Role Suggested For the Amygdala In Autismmentioning
confidence: 61%
See 2 more Smart Citations
“…Even though the hypothesis that the amygdala might underlie abnormal fear processing in autism has been brought forward recently (Amaral et al, 2003;Schumann and Amaral, 2006), the present study is the first to show that fear memories are greatly enhanced, overly generalized to novel stimuli, and harder to extinguish in an animal model of autism. These results are in fact also consistent with some less cited autistic features such as enhanced fears and phobias originally described by Kanner (1943) and reported in some more recent studies (Muris et al, 1998;Gillott et al, 2001;Evans et al, 2005).…”
Section: A Novel Role Suggested For the Amygdala In Autismmentioning
confidence: 61%
“…Both microscopic and macroscopic studies reveal alterations in the morphology of the amygdala in autism (Kemper and Bauman, 1998;Aylward et al, 1999;Sparks et al, 2002;Schumann et al, 2004;Schumann and Amaral, 2006), indicating a dysfunction in this region that might possibly contribute to the autistic pathology. The current 'amygdala theory of autism' is based on the lost capability to evaluate socioemotional information and lost drive for social interaction derived from lesioning studies in monkeys and a few functional imaging studies in humans (Baron-Cohen et al, 2000;Sweeten et al, 2002;Pelphrey et al, 2004;Bachevalier and Loveland, 2006;Schultz, 2005), which implies that a hypofunctioning amygdala underlies autism.…”
Section: A Novel Role Suggested For the Amygdala In Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we chose the left amygdala in this study, the side of the amygdala that plays a greater role in individuals with autism is not yet clear. Schumann and Amaral reported significantly fewer neurons in the bilateral amygdalae of the postmortem autistic brain (18).…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, an analysis of 12 MRI studies showed that by adolescence, the difference in brain volume between autistic individuals and controls was only 1 to 2 % [55]. Volumetric changes such as these likely provoked Schumann and Amaral [58] to quantitatively measure and compare the number of amygdalar neurons in post mortem autistic and control brains. Using stereological methods, they found a significant reduction in neuronal number in both the total amygdala and in the lateral nucleus of autistic individuals.…”
Section: The Amygdala Engrailed and Autismmentioning
confidence: 99%